Vein Texture Extraction Using the Multiscale Second-Order Differential Model - Xiong Xinyan; Fu Bin; Wang Kejun; Liu Fangming; Lv Zuowen (Institute of Advanced Engineering and Science, 2013)
In order to analyze the back of hand vein pattern rapidly and effectively, a novel approach based on multi-scale second-order differential model is proposed to extract the vein texture from vein samples directly, which is made up of two section: one is the foundation of local second-order differential model of vein texture(VLSDM), the other is texture extraction based on the multi-scale VLSDM. This paper analyzes the vein extraction using the multi-scale VLSDM and handles the filter response using the method of multi-scale analyzed noise filtered. This new algorithm has achieved good results for the vein texture, which is fuzzy, uneven distributed and cross-adhesion. Additionally this method keeps the original form of local shape and achieves orientation and scale information of the vein texture. The experiment result getting from this new method has also compared with another method and shown its outstanding performance. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3658